Expression Profiles of mRNA and lncRNA in HCT-8 Cells Infected With Cryptosporidium parvum IId Subtype - Liu, Ting-Li; Fan, Xian-Chen; Li, Yun-Hui; Yuan, Ya-Jie; Yin, Yan-Ling; Wang, Xue-Ting; Zhang, Long-Xian; Zhao, Guang-Hui (Frontiers in Microbiology, 2018)
Cryptosporidium parvum is one of the most important enteric protozoan pathogens, responsible for severe diarrhea in immunocompromised human and livestock. However, few effective agents were available for controlling this parasite. Accumulating evidences suggest that long non-coding RNA (lncRNA) played key roles in many diseases through regulating the gene expression. Here, the expression profile of lncRNAs was analyzed in HCT-8 cells infected with C. parvum IId subtype using microarray assay. A total of 821 lncRNAs and 1,349 mRNAs were differentially expressed in infected cells at 24 h post infection (pi). Of them, all five types of lncRNAs were identified, including 22 sense, 280 antisense, 312 intergenic, 44 divergent, 33 intronic lncRNAs, and 130 lncRNAs that were not found the relationship with mRNAs’ location. Additionally, real-time polymerase chain reaction of ten lncRNAs and ten mRNAs randomly selected were successfully confirmed the microarray results. The co-expression and target prediction analysis indicated that 27 mRNAs were cis-regulated by 29 lncRNAs and 109 were trans-regulated by 114 lncRNAs. These predicted targets were enriched in several pathways involved in the interaction between host and C. parvum, eg. hedgehog signaling pathway, Wnt signaling pathway and tight junction, suggesting that these differentially expressed lncRNAs would play important regulating roles during the infection of C. parvum IId subtype.